AN ANALYSIS OF STUDENTS’ ERRORS IN TRANSFORMING ACTIVE TO PASSIVE SENTENCE AT THE FOURTH SEMESTER OF STKIP MUHAMMADIYAH BOGOR - Lina Septianasari (JELLi Journal, 2021)
Passive voice is one of the important English grammars that should be mastered because it is used in formal and on informal language. The students tend to make some grammatical errors in transforming active to passive sentence. The objectives of this research are to know the types of errors that students made in transforming active to passive sentence, to know the students problems in transforming active to passive sentence and to know the proportion of the students’ errors. The subject of this research is 20 English students at the fourth semester of STKIP Muhammadiyah Bogor. The result of this research shows that the total number of errors that have been committed by the students based on surface strategy taxonomy is 280 errors, which falls into the following proportion of the four kinds of errors in surface strategy taxonomy: 126 errors of omission error, 18 errors of addition error, 120 errors of misformation error, and 16 errors of misordering error.